Lazaroid (U-74389G) ameliorates lung injury due to lipid peroxidation and nitric oxide synthase-dependent reactive oxygen species generation caused by remote systematic ischemia-reperfusion following thoracoabdominal aortic occlusion - Perlikos,F.; Lagiou, M.; Papalois, A; Rizou,T.; Kroupis, C.; Toumpoulis,I.K. (Int.J.Surg., 2018)
INTRODUCTION: Lung ischemia-reperfusion injury after thoracoabdominal aortic occlusion represents a major complication, which increases morbidity and mortality. In the present study we hypothesized that lazaroid U-74389G intravenous administration protects from lung ischemia-reperfusion injury through lipid peroxidation inhibition. MATERIALS AND METHODS: A total of 24 pigs were randomized in three groups. Group I (n=8) underwent sham operation, group II (n=8) underwent thoracoabdominal aortic occlusion for 45min and received placebo and group III (n=8) received 3 doses of lazaroid (3mg/kg) 60 and 30min before thoracoabdominal aortic occlusion and at 30min during thoracoabdominal aortic occlusion (duration 45min). Aortic occlusion was performed with aortic balloon-catheters under fluoroscopic guidance. All animals were sacrificed at the 7th postoperative day and lung specimens were harvested for molecular analysis. RESULTS: mRNA levels of leukotrienes LB4 (LTB4R2), LC4 (LTC4S) and nitric oxide synthase (NOS) isoforms including iNOS, nNOS and eNOS were determined with real-time RT-qPCR. Nitric oxide can either induce (iNOS) or inhibit (nNOS and eNOS) lipid peroxidation based on its specific isoform origin. Group III showed significantly reduced mRNA levels of LTB4R2 (-63.7%), LTC4S (-35.9%) and iNOS (-60.2%) when compared with group II (P < 0.05, for all). The mRNA levels of nNOS was significantly increased (+37.4%), while eNOS was slightly increased (+2.1%) in group III when compared with group II (P < 0.05 and P = 0.467 respectively). CONCLUSION: Lazaroid U-74389G may represent an effective pharmacologic intervention in reducing lung ischemia-reperfusion injury following thoracoabdominal aortic occlusion
Keywords: analysis; Animals; Antioxidants; Aorta,Thoracic; Arterial Occlusive Diseases; chemical synthesis; Complications; Disease Models,Animal; drug effects; Drug Therapy; Etiology; Greece; Lipid Peroxidation; Lung Injury; Male; metabolism; mortality; Nitric Oxide Synthase Type I; Nitric Oxide Synthase Type II; Nitric Oxide Synthase Type III; pharmacology; Pregnatrienes; Reactive Oxygen Species; Reperfusion Injury; Swine